Targeting tumor cell-derived CCL2 as a strategy to overcome Bevacizumab resistance in ETV5(+) colorectal cancer - Feng, Haoran (Cell Death Dis, 2020)
In our previous study, ETV5 mediated-angiogenesis was demonstrated to be dependent upon the PDGF-BB/PDGFR-β/Src/STAT3/VEGFA pathway in colorectal cancer (CRC). However, the ability of ETV5 to affect the efficacy of anti-angiogenic therapy in CRC requires further investigation. Gene set enrichment analysis (GSEA) and a series of experiments were performed to identify the critical candidate gene involved in Bevacizumab resistance. Furthermore, the ability of treatment targeting the candidate gene to enhance Bevacizumab sensitivity in vitro and in vivo was investigated. Our results revealed that ETV5 directly bound to the VEGFA promoter to promote translation of VEGFA. However, according to in vitro and in vivo experiments, ETV5 unexpectedly accelerated antiVEGF therapy (Bevacizumab) resistance. GSEA and additional assays confirmed that ETV5 could promote angiogenesis by inducing the secretion of another tumor angiogenesis factor (CCL2) in CRC cells to facilitate Bevacizumab resistance. Mechanistically, ETV5 upregulated CCL2 by activating STAT3 to facilitate binding with the CCL2 promoter. ETV5 induced-VEGFA translation and CCL2 secretion were mutually independent mechanisms, that induced angiogenesis by activating the PI3K/AKT and p38/MAPK signaling pathways in human umbilical vein endothelial cells (HUVECs). In CRC tissues, ETV5 protein levels were positively associated with CD31, CCL2, and VEGFA protein expression. CRC patients possessing high expression of ETV5/VEGFA or ETV5/CCL2 exhibited a poorer prognosis compared to that of other patients. Combined antiCCL2 and antiVEGFA (Bevacizumab) treatment could inhibit tumor angiogenesis and growth more effectively than single treatments in CRCs with high expression of ETV5 (ETV5(+) CRCs). In conclusion, our results not only revealed ETV5 as a novel biomarker for anti-angiogenic therapy, but also indicated a potential combined therapy strategy that involved in targeting of both CCL2 and VEGFA in ETV5(+) CRC.